The Impact of Illiberal Regional Powers in the Western Promotion of Democracy in Russia and China Region: Russia and China in Perspectives - OMOWAYEOLA, GABRIEL OLABODE (İstanbul Kültür Üniversitesi, 2022)
Huntington (1991:13) in his 'Third Wave: Democratization in the Late Twentieth Century' presented three waves of democratization: the 'slow' wave of the 19th century in Western Europe and Northern America, the wave after WWII in 1945, and the mid-1970s in Southern Europe. There were democratic gains after the Revolutions of 1989 which culminated in the fall of the Iron Curtain. However, according to Freedom House reports, democracy growth has not only slowed alarmingly, but is on the decline, particularly in Russian and China regions. This study first argues that Russia and China weaponize their economic and military rise against democracy promotion. The second argument is that advanced democracies leave open domestic democratic weaknesses for Russia and China to exploit. This study seeks to examine the strategies of Russia and China in limiting democracy promotion in Ukraine and Georgia (Russian region), and Hong Kong and Taiwan (China region). The overall aim is to understand the model of democracy promotion necessary for the Russian and Chinese impact.
Rusya ve Çin Bölgesinde Batı Demokrasisinin Desteklenmesinde İlliberal Bölgesel Güçlerin Etkisi: Perspektiflerde Rusya ve Çin
▪ Yüksek lisans tezi.